Effect of Season on some Biochemical Components of The Ovarian Follicular Fluid in Local Iraqi Ewes (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
This study was conducted in the technical college of Mussaib / department of Animal Production Techniques to investigate the effect of season on some follicular fluid biochemical parameters in the ovaries of the- . Fifty ovaries were collected from Karbala and Najaf butcheries for two seasons: the first season (August 2021) and the second season (January 2022). Moreover, collected follicles were divided according to their sizes into three groups (first group < 3 mm), (second group 3-5 mm), and (third group > 5mm) The results showed a significant increase (P ≤ 0.01) for protein, glucose, cholesterol, and sodium, and a significant increase (P ≤ 0.05) for calcium in the first season compared to the second season, and the significant increase was (P ≤ 0.05) for potassium in the second season compared to the first season. As for the follicles sizes the result exhibited, there were highly significant differences in the size of the follicles for the first group (< 3 mm ) P≤0.01, as it reached in the first season 8 (32.00%) and in the second season 13 (52.00%) and also found highly significant differences in the size of the follicles for the second group (3-5 mm) 11 (44.00%) in the first season and 6 (24.00%) in the second season (P≤0.01). for the follicles of the third group (> 5mm), there were no significant differences, as it reached 6 (24.00%) in the first season and 6 (24.00%) in the second season. The groups also differed significantly within the same season. The highly significant increase for the second group was (P≤0.01) compared to the rest of the groups within the first season, while in the second season, the high significant increase was for the first group (P≤0.01) compared to the rest of the groups.